A Comprehensive Measure of the Costs of Caring for a Parent: Differences According to Functional Status. Issue 10 (17th September 2018) - Coe, Norma B.; Skira, Meghan M.; Larson, Eric B.
Abstract : Approximately 34 million family and friends provided unpaid care to individuals aged 50 and older in 2015. It is difficult to place a value on that time, because no payment is made to the caregiver, and multiplying caregiving hours by a wage does not account for the value of lost leisure time, implications for future employability and wages, or any intrinsic benefits accrued to the care provider. This study used a dynamic discrete choice model to estimate the costs of informal care provided by a daughter to her mother, including these other costs and benefits not typically accounted for, and compared these cost estimates for 4 categories of the mother's functional status: doctor‐diagnosed memory‐related disease, limitations in activities of daily living (ADLs), combination of both, cannot be left alone for 1 hour or more. We studied women aged 40 to 70 with a living mother at the start of the sample period (N=3, 427 adult daughters) using data from the Health and Retirement Study (1998–2012). The primary outcome was the monetized change in well‐being due to caregiving, what economists call "welfare costs." We estimate that the median cost to the daughter's well‐being of providing care to an elderly mother ranged from $144, 302 to $201, 896 over 2 years, depending on the mother's functional status. These estimates suggest that informal care cost $277 billion in 2011, 20% more than estimates that account only for current foregone wages.